The function of controlling constituents for subject deletion in subordinative constructions in Acehnese - Iqbal, Muhammad; Mulyadi; Basaria, Ida; Dardanila (TALENTA, 2025)
This study aims to find the function of controlling constituents in Acehnese subordinative constructions. The function in question is “places” in the syntactic structure that will be filled with specific categories. This research employs qualitative research methods, incorporating note-taking and document review techniques. The data is presented in written text, rather than numbers or statistics. The data is obtained from various sources, such as sentences in Aceh language books, Aceh grammar books, and Aceh language dictionaries. The results show that controlling constituents in Acehnese subordinative constructions occupy only the functions of subject, object, complement, and adverb. These functions play a crucial role in connecting the main clause and the subordinate clause, thereby determining the overall meaning of the sentence. The subject-controlling constituent, as subject, object, complement, or adverb, plays a direct role in connecting the main clause and the subordinate clause. The subject in the subordinate clause refers to the subject, object, complement, and adverb in the main clause so that the subject in the subordinate clause can be omitted. It can be said that all these syntactic functions play an important role in controlling the subject in the subordinate clause.